Relationships among open innovation, innovative performance, government support and firm size: Comparing Brazilian firms embracing different levels of radicalism in innovation - Jugend, Daniel [UNESP] (2018)
This work extends knowledge concerning the relationships among open innovation, innovative performance and government support for innovation within Brazilian firms. Data were obtained from two different firm samples (Sample A, on incremental innovation, and Sample B, on radical innovation). The main research results are as follows. First, in considering government support for innovation, Sample B, based on radical innovation, played a superior and stronger role than Sample A. Secondly, for both samples, the cooperation of external firms has a positive effect on firms’ innovative performance, which was positively controlled by the size of the firms. Thirdly, in general, radical innovation requires synergy and a more intense focus regarding the constructs considered therein. This work also adds value in methodological terms, as this is the first research to have tested different models of samples with different levels of radicalism in innovation.